Preparing and Motivating Seventh Graders of Indonesian Junior High School to Learn English through a Pre-Vocabulary Instruction Program - Septhia Irnanda (Jurnal Dedikasi Pendidikan, 2021)
Indonesia curriculum has delayed English subject introduction until at least the student completes their primary level (aged 12). Starting English class with minimum vocabularies, the student is confronted to learn from authentic texts full of words they know not the meaning, nor the way to pronounce it right. The aim of the article is to discuss the motivational problem faced by the Indonesian Junior High School students as the beginners of English learners, particularly regarding their basic knowledge of English words that is important to help them feeling confident and positive during the first years of learning. The article proposes that some pre-vocabulary lessons should be given to students before or along the first year in Junior High School level.